La condición física de estudiantes de bachillerato de la unidad educativa “Alfonso Herrera” y su percepción de las clases virtuales de educación física durante en el confinamiento. - Ruales, Luis E. (2022)
The CODID-19 pandemic forced educational institutions to carry out their academic activities through virtual means, perhaps one of the subjects that had the greatest difficulty of adaptation and objectivity in measuring their results was physical education; for this reason, this study was conducted with the purpose of knowing: the physical condition of the students of the unified general high school of the Millennium Educational Unit "Alfonso Herrera" during the confinement, and the development of virtual physical education classes in this period. The study had a quantitative-descriptive approach, in which one hundred and seven students participated, to whom the "Burpees" test was applied to know their physical condition; and to know the factors that influenced the harmonic development of the physical activities proposed by their teachers during the confinement, a survey of eight questions was applied. The results obtained determine that although the physical condition of many students is acceptable, there is an important group of students with whom it is necessary to work in the classroom to improve their physical and mental condition. The study also determines that although there were connectivity problems and methodological adaptations to teach physical education during the COVID-19 pandemic, the students accepted this modality in an acceptable way, participated in classes and obtained knowledge and developed physical exercises that allowed most of them to maintain a good physical and mental condition; reiterating that there is an important group of students who should be taken into account to level their physical abilities.